2011
DOI: 10.1074/jbc.m110.169342
|View full text |Cite
|
Sign up to set email alerts
|

S100B Protein Stimulates Microglia Migration via RAGE-dependent Up-regulation of Chemokine Expression and Release

Abstract: The Ca 2؉ -binding protein of the EF-hand type, S100B, is abundantly expressed in and secreted by astrocytes, and release of S100B from damaged astrocytes occurs during the course of acute and chronic brain disorders. Thus, the concept has emerged that S100B might act an unconventional cytokine or a damage-associated molecular pattern protein playing a role in the pathophysiology of neurodegenerative disorders and inflammatory brain diseases. S100B proinflammatory effects require relatively high concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
177
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(188 citation statements)
references
References 85 publications
10
177
0
1
Order By: Relevance
“…According to these studies, a close relationship exists between TNF-α and S100B levels in brain tissues, and typically, these levels are altered accordingly (22,55,56). In our study, the hippocampus TNF-α levels were increased while the S100B levels were inversely reduced as a result of chronic morphine exposure.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…According to these studies, a close relationship exists between TNF-α and S100B levels in brain tissues, and typically, these levels are altered accordingly (22,55,56). In our study, the hippocampus TNF-α levels were increased while the S100B levels were inversely reduced as a result of chronic morphine exposure.…”
Section: Discussionsupporting
confidence: 55%
“…The S100B levels in hippocampus tissue and cerebrospinal fluid increase during brain damage or pathophysiological situations, and the consequent behavioral symptoms (28,30,(54)(55)(56)(57) might be induced by glial cell activation through the RAGE-dependent pathway (22,58). According to these studies, a close relationship exists between TNF-α and S100B levels in brain tissues, and typically, these levels are altered accordingly (22,55,56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar responses have been reported that Rac1 involved in regulating MAPK activation through p21-activated kinases 36 or JNK/AP1 pathway. 37 In contrast, FSP-1-stimulated Rac1 activation could not be inhibited by negative dominant MEK5, suggesting that Rac1 acts as an upstream of ERK5.…”
Section: Discussionmentioning
confidence: 92%
“…This may indicate an additional RAGE-, TLR-2-, or other receptor-dependent cytokine activating pathway. In this context, Bianchi et al showed a RAGE-dependent up-regulation of chemokines, including RANTES and MIP-1α, in microglia (48). Another study showed that an HMGB1-nucleosome complex mediated inflammatory cytokine activation through TLR-2 (46).…”
Section: Discussionmentioning
confidence: 99%